Meta-Analysis Study: Selection of Long-Acting Contraceptive Methods - Dita Apriliana Sari; Meitria Syahadatina Noor; Eko Suhartono; Syamsul Arifin; Silvia Kristanti Tri Febriana (Journal of Management Practices, Humanities and Social Sciences, 2024)
Births are controlled by the Family Planning Program. Most women of childbearing age are at a loss to choose contraception. Many women not using contraception because of the lack of information about contraception that is right for them. This causes uncontrolled births and increases maternal morbidity and mortality. Based on preliminary studies in several journals, there are inconsistencies or differences in research results on the variables of between knowledge and age with the selection of long-acting reversible contraceptives. Analyzing the greater relationship between knowledge and age with the selection of long-acting reversible contraceptives.: Meta analysis by searching the Google Scholar and NCBI. After going through the identification and selection stage, 20 articles were included in the meta-analysis. Pooled Odds Ratio (pOR) is calculated using a fixed-effect model for data analysis according to the heterogeneity test using Review Manager 5.4.1. The pOR value for the knowledge variable is 1,76 (95% CI 1,31-2.37) with a mean effect size value of 0,4888 and for the age variable 1,15 (95% CI 0,088- 1,51) with a mean value effect size of 0,4056. The knowledge variable has a greater than a age variable.